Relation Of Government Organizational Performance With Their External Stakeholder Satisfaction: A Qualitative Study In The Municipal Of Enrekang, Provinces Of South Sulawesi, Indonesia - Siti Farisya; Idayanti Nursyamsi; Erlina Pakki (Cita konsultindo, 2023)
Attainment of organization performance relates to participation of its external stakeholder. External stakeholder here defined as the group which having importance with organization and cannot be controlled by organization management. Existence of external stakeholder becomes of vital importance and influential to performance and continuity of organization life (Kasali, 1990). Therefore, management of the government organization needs to paying attention more to the importance of the external stakeholder. External stakeholders that become the focus in this paper are supplier/partners, citizens, and the activist group.